DEVELOPING EASTERN : INDONESIA CUSTOMS PRE-INSPECTION FACILITY IN DARWIN, A FAILED STORY ? - Afriansyah Darwin (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
This study will describe the background of indonesian Customs pre-inspection facility in darwin (ICPIF), the Implementation of the tasks carried out by the official from time to time and try to indentify the causes resulted in the ICPIF break-off. The research conducted by field research and literature study. The objective of ICPIF was to facilitate preinspection on goods to be exported from port or airport at darwin to any port in Indonesia except those located in island of java and Sumatra. Customs Officials had carried this Facility since August 2002. Since then, it is recorded that the exporters and exportations utilize the facility is up and down . After the deferral period, which lasted more than one year ( October 2013 until December 2014), the facility is now no longer establized. The shut-up happened due to slacking the used of the study recommed the ministry of finance and directorate General of Customs and Excise to further study the possibility of commencing preinspection coorperation with neighboring countries to expedite the flow of import goods in the port of destination . This activity will also reduce the dwell time of import goods.